2010
DOI: 10.1152/ajpcell.00057.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vimentin intermediate filaments in endothelial cells by hypoxia

Abstract: Hypoxia triggers responses in endothelial cells that play roles in many conditions including high-altitude pulmonary edema and tumor angiogenesis. Signaling pathways activated by hypoxia modify cytoskeletal and contractile proteins and alter the biomechanical properties of endothelial cells. Intermediate filaments are major components of the cytoskeleton whose contribution to endothelial physiology is not well understood. We have previously shown that hypoxia-activated signaling in endothelial cells alters the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 24 publications
7
60
0
1
Order By: Relevance
“…Consistent with this premise, vimentin protein levels were significantly increased in the carotid artery and aortic arch of suprarenal abdominal aortaconstricted rats in this study, and a positive correlation was observed between the magnitude of expression and MAP and LVSP in the carotid artery alone. Thus, since vimentin expression has been reported in endothelial and vascular smooth muscle cells, both cell types may have contributed to the reported upregulation in the vasculature of banded rats (15,19).…”
Section: Discussionmentioning
confidence: 94%
“…Consistent with this premise, vimentin protein levels were significantly increased in the carotid artery and aortic arch of suprarenal abdominal aortaconstricted rats in this study, and a positive correlation was observed between the magnitude of expression and MAP and LVSP in the carotid artery alone. Thus, since vimentin expression has been reported in endothelial and vascular smooth muscle cells, both cell types may have contributed to the reported upregulation in the vasculature of banded rats (15,19).…”
Section: Discussionmentioning
confidence: 94%
“…Vimentin has been reported to be phosphorylated upon p38 activation, and recent studies demonstrate that the p38-hsp27 pathway affects vimentin expression and filament assembly (Liu et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The assembly dynamics of vimentin IFs are controlled by phosphorylation status (43), as seen by fluorescent imaging of live cells, and are capable of assembling and disassembling rapidly in response to external stimuli, such as tumor-associated hypoxia (44). In addition, vimentin has been shown to be phosphorylated by protein kinase A at Serines 38 and 72, which leads to decreased filament formation in vivo.…”
Section: Assembly Dynamics Of Vimentinmentioning
confidence: 99%